Calcium signals are necessary to establish auxin transporter polarity in a plant stem cell niche - Ting Li (Nature Portfolio, 2019)
Auxin transport and microtubule orientation respond to mechanical stimulation at the shoot apical meristem. Here Li et al. show that mechanical stimulation causes cytosolic calcium concentration transients, and preventing such changes impairs reorientation of the PIN1 auxin efflux carrier, but not of microtubules.